Severe Typhoid Fever Complicated by Superior Mesenteric and Splenic Vein Thrombosis - Piero Veronese; Marco Pappalardo; Valentina Maffini; Monica Rubini; Alessandra Giacometti; Maria Beatrice Ruozi; Simone Cella; Icilio Dodi (MDPI AG, 2023)
Typhoid fever (Typhoid or enteric fever) is still the most common bacterial bloodstream infection worldwide, caused by Salmonella typhi. The transmission route is indirect through passive vehicles such as contaminated water or food. Main clinical findings are a fever lasting more than three days, abdominal symptoms, leukocytosis, and anemia. Typhoid can cause a wide range of multi-organ complications. We report a particularly severe form of this infection complicated by superior mesenteric vein and splenic vein thrombosis, an extremely uncommon manifestation.